The critical success factors of cloud based application implementation in construction management / Mohd Asfahani Sukiman - Mohd Asfahani, Sukiman (2020)
Design and construction are information intensive activities, involving a great number of people collaborating to produce complex, one-off developments. Whilst historically, information may have been managed and communicated using paper-based systems and verbal instructions, the integration of the supply chain, the introduction of computer aided design (CAD) and building information modelling (BIM) and the development of cloud computing application means that information communications technology (ICT) is becoming a fundamental part, not just of the design office, but also of the construction site. Cloud computing is a relatively new phenomenon in the construction industry. It allows the delivery over the 'cloud' (the internet) of a range of computing services, such as storage, databases, networking, servers, software and analytics to allow building professionals access to faster and more flexible information resources. However, the absence or lack of legal and regulatory support as well as guidelines on implementation of cloud-based application in the construction industry has become a hindrance for its adoption. In this research, the critical success factors for cloud-based application implementation are analysed, as well as its impact to project success. Through literature review, the critical success factors, the application software and tools are identified. Furthermore, a survey is conducted, to get an overall overview on the utilization of cloud-based application among construction professionals as well as on the effective critical success factors for implementation. The research then concluded the impact that cloud-based application has to project success. Keywords: construction, cloud computing, information communication technology